2022
DOI: 10.3389/fphar.2021.788874
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Venom Antimicrobial Peptides Induce Caspase-1 Dependant Pyroptotic Cell Death

Abstract: Within the last decade, several peptides have been identified according to their ability to inhibit the growth of microbial pathogens. These antimicrobial peptides (AMPs) are a part of the innate immune system of all living organisms. Many studies on their effects on prokaryotic microorganisms have been reported; some of these peptides have cytotoxic properties although the molecular mechanisms underlying their activity on eukaryotic cells remain poorly understood. Smp24 and Smp43 are novel cationic AMPs which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…DAPI, cyclosporin A (CsA, an inhibitor of permeability transition), N-acetyl-L-cysteine (NAC), ROS assay kit, LDH-release assay kit, cell cycle and apoptosis analysis kit, and mitochondrial membrane potential assay kit for JC-1 were bought from Beyotime Institute of Biotechnology (Shanghai, China). Smp24 and FITC-labeled Smp24 were obtained as previously described by us [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DAPI, cyclosporin A (CsA, an inhibitor of permeability transition), N-acetyl-L-cysteine (NAC), ROS assay kit, LDH-release assay kit, cell cycle and apoptosis analysis kit, and mitochondrial membrane potential assay kit for JC-1 were bought from Beyotime Institute of Biotechnology (Shanghai, China). Smp24 and FITC-labeled Smp24 were obtained as previously described by us [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported Smp24 (IWSFLIKAATKLLPSLFGGGKKDS), a cationic AMP identified from the venom of Scorpio Maurus palmatus with a wide antimicrobial spectrum against various bacteria and fungi [ 8 ]. The cytotoxicity of Smp24 against two acute leukemia cell lines (KG1-a and CCRF-CEM), as well as four lung cancer cell lines (A549, H3122, PC-9, and H460) and nontumor cell lines (HRECs, CD34 + , MCR-5, and HaCaT) has been described in further studies [ 9 , 10 , 11 ]. Smp24 also has cytotoxic effects against HepG2 hepatoma cells, as presented in ATP release assays; nevertheless, its mode of action against HepG2 hepatoma cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[51] The antimicrobial Smp24 is a peptide derived from the venom of Scorpio maurus palmatus that has a 54 % homology with Pin 2 and has anticancer effects in acute leukemia (myeloid KG1-a) and lymphoid (CCRF-CEM) cells as well as in hepatoma (HepG2) and lung adenocarcinoma (A549) cells which may indicate that Pin2 also possesses anticancer activities. [52][53][54][55] To understand the importance and role of a specific amino acid sequence (ETFS) that is present in some peptides derived from the p53-MDM2 complex (these instigate cytotoxicity in cancer cell lines), eleven peptides were analyzed, where 4 peptides had amino acid exchanges and additions. With this, they observed that the exchange of isoleucine for a valine led to the formation of a smaller alpha-helix and that the addition of amino acids to the fragment (-ETFS-) favors intermolecular interactions, increasing the formation of hydrogen bridges, which leads to greater stability of alpha-helices.…”
Section: Optimizing the Design Of New Peptidesmentioning
confidence: 99%
“…Chitosan enjoys many benefits, especially while creating nanoparticles; among these, are its capacity to control the arrival of dynamic specialists, aversion to the utilization of dangerous natural solvents while manufacturing particles, its cationic nature, and its mucoadhesive person which increments remaining time at the site of ingestion (Islam, Bhuiyan and Islam, 2017). For insurance and prey catch, the venom apparatus of scorpions produce venom, which is a combination of proteins (synthetics and peptides) and non-proteins like inorganic salts, lipids, nucleotides, free amino acids, and water-based compounds (Gopalakrishnakone et al, 2015 andElrayess et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the peptides in scorpion venom are disulfide and non-disulfide spread over, and a few of them have been displayed to have hostile to epileptic, hemolytic, against thrombotic, relieving, antibacterial, and anticancer properties (Elrayess et al, 2022;Mishal et al, 2013;Ortiz et al, 2015;Attarde and Pandit, 2016;Salem et al, 2016;Tobassum et al, 2018 ;Shah et al, 2018;Akef, 2019;Ahmadi et al, 2020;Díaz-García and Varela, 2020).…”
Section: Introductionmentioning
confidence: 99%